MOTIVATION AND SOCIAL SUPPORT AS DETERMINANTS OF SELF-PERCEIVED ACHIEVEMENT AMONG MALAYSIAN UNIVERSITY ATHLETES - Aziz, Nur Aina A.; Koh Choon Lian, Denis; Nazarudin, Mohamad Nizam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study examines the combined influence of motivation and social support on self-perceived achievement among Malaysian university athletes, grounded in Self-Determination Theory (Deci & Ryan, 1985), Social Support Theory, and Self-Appraisal Theory. A quantitative cross-sectional survey was conducted with 100 student-athletes (52 males, 48 females) from Malaysian public universities participating in national collegiate competitions. Data were collected using the Sport Motivation Scale-II (SMS-II), the MOS-Modified Social Support Survey (MOS-SSS), and the Sport Performance Perception Scale (SPPS). Reliability coefficients were satisfactory (α = .85–.86). Descriptive statistics, Pearson correlations, and multiple linear regression analyses were performed using SPSS 26. Results indicated that both motivation (r = 0.63, p < 0.01) and social support (r = 0.58, p < 0.01) were strongly correlated with self-perceived achievement. The regression model was significant (F(2, 97) = 46.8, p < .001) and explained 49 % of the variance, with motivation (β = .45) emerging as the strongest predictor, followed by social support (β = .38). The findings confirm that athletes with higher intrinsic motivation and greater perceived support exhibit stronger confidence, satisfaction, and performance appraisal. The study provides empirical validation of SDT in a dual-career university context and underscores the psychosocial synergy between internal drives and environmental resources in sustaining athletic excellence. It advocates for integrating motivational coaching, mentorship, and structured social support mechanisms into Malaysian higher education sport programs to optimize both athletic and academic outcomes.